Weathering degradation of polyester and polypropylene geotextiles - Lodi, P. C. [UNESP]; Bueno, B. S.; Vilar, O. M.; Correia, N. S. [UNESP] (Springer Nature, 2008)
This paper presents results of physical and mechanical tests in polyester (PET) and polypropilene (PP) nonwoven geotextiles that were exposed to weathering conditions (solar radiation, humidity, wind, rain) after some specific periods of exposure (1, 2, 3 and 4 months). ASTM D5970 and Brazilian standards (NBR) recommendation were followed in this research. Results show variations in tensile properties and in the mass per unit area. Variations in the deformations were more significant in the PP geotextile when compared to the PET geotextile.
Keywords: Degradation; Geotextiles; Mechanical properties; Weathering exposure